Cervicitis, and its agents in the pap smear routine - Tavares, Thais G; Krunn, Patrícia; Costa, Eglon Inácio; Padilha, Cátia ML; Pinto, Álvaro P (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: cervicitis is one of the most controverse topics in cervical pathology and it’s definition vary so much according to clinical, citologic,colposcopic and histologic aspects. In the last years, the colpocytologic test (pap smear) has been used in the screening of vaginal leucorrhea becauseof its capacity to identify biologics agents. Objectives: considering the capacity of the pap test to identify biological agents and that the most frequentsign present in the ambulatorial gynecologic routine is leukorrhea, this article aims to find the prevalence of cervicitis and its infeccious agents in thepap smear routine.Methods:500 Pap smears from Divisão de Patologia do Instituto Nacional do Câncer (DIPAT-INCA) were analised. 171 (34,2%)cases with absence of endocervical cells were excluded. The criteria used for the diagnosis of cervicitis were: 1) the presence of metaplastics andglandular cells with inflamatory alterations – metacromasia, binucleation or multinucleation, nuclear enlargment and proeminent nucleolus; 2) theintensity of the exudates; and 3) the amount of cervical mucus present in the slide. Results: from 329 cases analised, 207(63%) showed cervicitis.The age ranged from 15 to 74, with mean of 36 years old. Considering the criteria used for diagnosis, 98% of the cases showed metacromasia, 47,5%nuclear enlargment and 6,7% binucleation or multinucleation. None of the cases showed prominent nucleolus. Only 0,8% showed lymphocytic cervi-citis. According to the causal agents, 47% showed Doederlein bacili, 23,8% short bacili, 5,3% cocos, 7,7% mixt bacteria, 0,5% Chlamydia sp, 4,3%trichomoniasis and 2,4% candidiasis. Conclusion:the present study demonstrated the acuracy of Papanicolaou method for the diagnosis of cervicitisand the determination of the causal agent.